Persepsi dan tahap kesediaan guru Fizik dalam pelaksanaan PEKA di sekolah menengah daerah Pontian - Ting, Fang Ling (2013)
PEKA physics is a School Based Assessment which plays an important role in the education system in Malaysia. The purpose of this study was to find out the perception, readiness level of physics teachers in implementing the PEKA from the aspect of knowledge and skills in the management and assessment of PEKA as well as problems faced by physics teachers in the implementation of PEKA. A total of 30 physics teachers from 10 secondary schools in Pontian were selected as the respondents. An instrument in the form of questionnaire was used to collect data. The data was analyzed using descriptive statistics only. The study found that physics teachers showed a positive perception on the implementation of PEKA possessed a high level of readiness in term of knowledge and a moderate level of readiness in term of skills. Besides, the main problems faced by the physics teachers were inadequate apparatus and materials as well as difficult to get the references on reference about PEKA assessment. Hence, this study can help to enlighten teachers to raise the level of readiness in terms of knowledge and skills in implementing the PEKA at school through attending courses and workshops related to PEKA.